DERADIKALISASI PAHAM KEAGAMAAN MELALUI MODERASI BERAGAMA PADA MAHASISWA UIN RADEN FATAH PALEMBANG - Rohmadi Rohmadi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2021)
Prejudice and claims of universities as centers and seeds of radicalism emerged after the National Counterterrorism Agency (BNPT) released its research results. Although it needs to be tested methodologically, the research presented by BNPT creates a